The Influence of Digital Marketing and Service Quality on Customer Loyalty among Gojek Users (Case Study of FISIP Students at Riau University) - Annisya, Aulia Bani; Sutrisna, Endang (CV. Rayyan Dwi Bharata, 2024)
This research aims to identify and analyze the influence of digital marketing and service quality on customer loyalty among Gojek users, with a focus on students at the Faculty of Social and Political Sciences (FISIP) at Riau University. The research method used was a survey using a questionnaire distributed to respondents who were Gojek users among FISIP students at Riau University. The data analysis technique used is multiple linear regression. The results of this research show that digital marketing has a significant influence on customer loyalty among Gojek users among FISIP students at Riau University. Apart from that, service quality also has a significant influence on customer loyalty among Gojek users among FISIP students at Riau University. Thus, it can be concluded that both digital marketing and service quality have an important role in forming customer loyalty on the Gojek platform among FISIP students at Riau University. It is hoped that the findings from this research can contribute to the development of digital marketing strategies and improve service quality for Gojek and other similar companies in increasing customer loyalty, especially among FISIP students at Riau University and can also be a reference for further research in the same field.